DEVELOPMENT OF A SCIENCE LITERACY-BASED TEST INSTRUMENT TO MEASURE STUDENTS CRITICAL THINKING SKILLS ON THE MATERIAL OF TEMPERATURE AND HEAT - Nadila Nadila; Ridwan Abdullah Sani (Department of Physics Education, Faculty of Teacher Training and Education, UNIVERSITAS MA, 2026)
This study aims to determine the validity, reliability, level of difficulty, discriminating power, and critical thinking skills of students from the development of a scientific literacy-based test instrument to measure students' critical thinking skills in physics learning in high schools. This type of research is research and development (R&D) with the ADDIE model which has five stages, namely analyze, design, development, implementation, and evaluation. The subjects in this study were 25 students of class XI F1 A MAN 2 Model Medan. Data collection techniques carried out by researchers were validity, reliability, level of difficulty of questions, discriminating power, and analysis of students' critical thinking skills and participants' responses to the developed instrument. Theoretical validity analysis was carried out by physics experts, namely lecturers and teachers using a validation sheet. Empirical validity was calculated using the Point Biserial Correlation method in Microsoft Excel. The assessment instrument contained 20 questions. The results of theoretical validity obtained a value of 0.81 with very valid criteria. The results of empirical validity obtained 20 questions with 14 valid questions and 6 invalid questions. The reliability of the questions was 0.64 with a reliable category. The difficulty level of the questions showed 7 items in the easy category, 9 items in the medium category and 4 items in the difficult category and the discrimination power of the questions showed 7 questions in the good category, 8 questions in the sufficient category and 5 questions in the bad and very bad categories. Analysis of participant responses Participants were 75.12% which means that students gave a positive response to the literacy-based test instrument developed. The results of this study show that students have an average critical thinking ability in the low category with an average score of 59.6%.